Revision of the Australian sawfly genus Antargidium (Hymenoptera, Symphyta, Argidae) with description of two new species - Schmidt, Stefan (Zootaxa, 2012)
Antargidium Morice, 1919 is a small sawfly genus with six described species. The distribution is limited to Australia, withfour species occurring in eastern and two in the south-eastern part of Western Australia. Two species, A. flavescens n. sp.and A. nigrum n. sp., are described as new from Western Australia. Antargidium rufum Benson syn. nov. is treated as asynonym of A. dentivalve Benson. Host plants are known for five species and include plants of the families Sapindaceae and Leguminosae.